The Maintainability of Open Source Software - Hung, Yong Jing (2008)
The impact that OSS brings to the software economy should not be dismissible lightly. In a study by ANU-Merit (Ghosh, 2006), it revealed that OSS market share have seen considerable growth in the past five years. Based on the existing trend, the study predicts that OSS related services would gain 35% share of all IT services by the year 2010. With two thirds of free contributions coming from individuals, which is worth at least Euro 800million a year, companies may need to turn their heads to examine this option. This paper studies the maintainability of Open Source Software to provide managers with a set of tools to select maintainable products when compiling their product offerings, since OSS cannot be sold under the traditional license and support services is one way of profiting from Open Source. This is an effort to give managers a compass when embarking on the terrains of Open Source. Despite that the failure to identify a reliable and predictable factor of resolution time, this dissertation proves that software age, programming language, software complexity and the number of core maintainers in a project do not influence resolution time. The most significant discovery in this paper is how maintenance behaviour such as participation inequality and cross-bug connectivity influences the resolution of bugs. The result shows that participation inequality expedites defect fixing, and that there exists an optimal level of contributions, which influence the rate of resolution on feature requests. This Another discovery in this paper is the rate of response of the Open Source volunteers to bug resolution. Typically, it takes an average of over 40 days for maintainers to respond. So, for marketers of OSS support services, this presents a powerful message in their marketing campaign.